Effect of probiotics on the amount and pH of saliva in edentulous patients: A Prospective study - Urvi Sanghvi; Tamanna Chhabra; Rajesh Sethuraman (Wolters Kluwer Medknow Publications, 2018)
Context: Probiotics have been prescribed to old aged patients' invariably with or without complete dentures for improving their digestive process. It is mentioned that probiotics do have an effect in increasing the amount of saliva in the oral cavity. Therefore, this study was planned to evaluate the amount and pH of saliva after using probiotics for 60 days in completely edentulous patients. Aim: This study aims to evaluate the amount and pH of saliva of edentulous patients before and after using probiotics. Settings and Design: The interventional prospective study was conducted at the department of prosthodontics of the institute. Methods: The study was conducted on edentulous patients. The whole unstimulated and stimulated saliva was collected at baseline and amount, and pH was measured. Then, each patient was given probiotic capsules reaching 3.3 × 107 CFU/g to consume daily once for 60 days. Saliva was recollected from patients, and its amount and pH was calculated and compared with baseline. Statistical Analysis Used: STATAIC-13. Results: On comparison of saliva before and after consuming probiotics, there was an increase in the mean unstimulated and stimulated saliva from baseline to that after 60 days, the difference being 0.406 and 0.433, respectively. The difference was statistically significant with P < 0.001. The mean pH at baseline was 7.818 ± 0.231 which increased after 60 days to 7.825 ± 0.189, the difference being 0.007. Conclusion: This study concluded that probiotics increase the amount of saliva of completely edentulous patients and so it can be helpful in patients suffering from xerostomia/hyposalivation.